الادوار الجديدة للمنظمات الدولية المتخصصة في ظل المتغيرات الدولية الراهنة " محكمة العدل الدولية نموذجا - أمينة بونيف ● سمية بن شهبة (جامعة المسيلة, 2024)
The present study, labelled "New Roles of Specialized International Organizations", aims at current international variables The Israeli aggression against Gaza, where it can be generally said that specialized international organizations deal with many and many challenges where such challenges include armed conflicts; Humanitarian crises, climate change, migration, security threats, health challenges, and many more, It also promotes global peace and security and protects human rights, Promoting sustainable development, combating poverty and strengthening international cooperation in areas such as trade, environment, technology and culture Therefore, studying the role of specialized international organizations requires a thorough and comprehensive analysis of the specific challenges and changing global context, especially in the light of Israel's aggression against Gaza
Keywords: Role; specialized international organizations; current situations; International Court of Justice; Zionist aggression; Palestine